Transferring Gracilaria irregularis (Gracilariaceae, Rhodophyta) from Thailand to Gracilariopsis based on morphological and molecular analyses. Issue 1 (30th October 2013) - Muangmai, Narongrit; Yamagishi, Yukimasa; Zuccarello, Giuseppe C.; Chirapart, Anong; Lewmanomont, Khanjanapaj
Summary Gracilaria irregularis, endemic to Thailand, was originally described from Ao Len, Trat peninsula, Thailand, and was characterized by a short, succulent thallus with irregular branching, verrucosa‐type spermatangia (a taxonomic criterion for Gracilaria) and the absence of nutritive filaments (a taxonomic criterion for Gracilariopsis). Due to the combination of characters diagnostic of both the genera Gracilaria and Gracilariopsis, the taxonomic status of this species is unclear. This present study reassesses the identity of G. irregularis based on morphological features and the large subunit of ribulose‐bisphosphate carboxylase/oxygenase gene sequences. Newly collected samples from the type locality and KU collection were investigated. Our morphological re‐examinations were relatively similar to the original type description, except that the male plants showed superficial chorda‐type spermatangia, an important characteristic recognized in Gracilariopsis. Molecular analysis placed G. irregularis in the Gracilariopsis clade, forming a well‐supported clade with Gracilariopsis bailiniae. Detailed morphology and molecular phylogenetic analyses clearly showed that G. irregularis is congruous with the generic concept of Gracilariopsis, and consequently the new combination of Gracilariopsis irregularis is proposed. We believe that in the original description a heterogeneous holotype was used. Our data also shows the problems that can occur when collections are made of multiple plants, of similar external morphology, to describe new species.